MENDENGARKAN SEBAGAI MODEL KOMUNIKASI UNTUK MEMAHAMI REMAJA - Fabianus Fensi (Psibernetika, 2016)
Adolescence is full conflict period in the life of teens are signed by rebellion behavior dynamic and avoid order and social norms. Freedom become the main demands and family with their norms produced are seens as cause of their not free situations. Parents should be  understand  these problems as something that has to be faced, no judge them as disorder. By  the literature analysis this study recommends interpersonal communication model that is listening as the way to understand the  teens problems adequately. Listening communication give the parents change to take apart  in teens selfdevelopment empathicly. Keywords: adolescence; parents; interpersonal communication; listening